Lung Transplantation for Cystic Fibrosis: Results, Indications, Complications, and Controversies - Lynch, Joseph P., III; Sayah, David M.; Belperio, John A.; Weigt, S. Sam (Seminars in Respiratory and Critical Care Medicine, 2015)
Survival in patients with cystic fibrosis (CF) has improved dramatically over the past 30 to 40 years, with mean survival now approximately 40 years. Nonetheless, progressive respiratory insufficiency remains the major cause of mortality in CF patients, and lung transplantation (LT) is eventually required. Timing of listing for LT is critical, because up to 25 to 41% of CF patients have died while awaiting LT. Globally, approximately 16.4% of lung transplants are performed in adults with CF. Survival rates for LT recipients with CF are superior to other indications, yet LT is associated with substantial morbidity and mortality (∼50% at 5-year survival rates). Myriad complications of LT include allograft failure (acute or chronic), opportunistic infections, and complications of chronic immunosuppressive medications (including malignancy). Determining which patients are candidates for LT is difficult, and survival benefit remains uncertain. In this review, we discuss when LT should be considered, criteria for identifying candidates, contraindications to LT, results post-LT, and specific complications that may be associated with LT. Infectious complications that may complicate CF (particularly Burkholderia cepacia spp., opportunistic fungi, and nontuberculous mycobacteria) are discussed.
Keywords: lung transplant; cystic fibrosis; Burkholderia cepacia spp.